ANALISIS ONLINE IMPULSIVE BUYING PADA E-COMMERCE SHOPEE: FLASH SALE, SHOPEE PAYLATER, GRATIS ONGKOS KIRIM DAN ONLINE REVIEW CUSTOMER - Nailiya Fatma Ulya; Wibowo, Bambang Setia (LPPM STIE YKPN Yogyakarta, 2026)
This study aims to analyse the relationship between flash sale, shopee, paylater, free shipping, and online customer review on online impulsive buying behavior in Shopee application users. This study used purposive sampling as a method of collecting data through a questionnaire which obtained 157 respondents. The result of this study indicate that the variables of flash sale, shopee paylater, free shipping, and online customer review affect the variable online impulsive buying in Shopee application users. The result of this study can be used as a reference for ecommerce companies, especially the Shopee company to be able to improve the quality of its features, so that it will further encourage higher online impulsive buying behavior.